Rational Design of a Novel Tubulin Inhibitor with a Unique Mechanism of Action. Issue 25 (25th April 2022) - Mühlethaler, Tobias; Milanos, Lampros; Ortega, Jose Antonio; Blum, Thorsten B.; Gioia, Dario; Roy, Bibhas; Prota, Andrea E.; Cavalli, Andrea; Steinmetz, Michel O.
Abstract: In this study, we capitalized on our previously performed crystallographic fragment screen and developed the antitubulin small molecule Todalam with only two rounds of straightforward chemical synthesis. Todalam binds to a novel tubulin site, disrupts microtubule networks in cells, arrests cells in G2/M, induces cell death, and synergizes with vinblastine. The compound destabilizes microtubules by acting as a molecular plug that sterically inhibits the curved‐to‐straight conformational switch in the α‐tubulin subunit, and by sequestering tubulin dimers into assembly incompetent oligomers. Our results describe for the first time the generation of a fully rationally designed small molecule tubulin inhibitor from a fragment, which displays a unique molecular mechanism of action. They thus demonstrate the usefulness of tubulin‐binding fragments as valuable starting points for innovative antitubulin drug and chemical probe discovery campaigns. Abstract : Antitubulin drugs are used very successfully in chemotherapy but their chemical structures are complex. Based on a previously performed crystallographic fragment screen, we here rationally designed the small molecule tubulin inhibitor Todalam. The compound displays a unique molecular mechanism of action by targeting a novel binding site in tubulin.